Virtual Reality Terintegrasi Cognitive Theory of Multimedia Learning (CTML) Pada Gelombang Cahaya & Bunyi: Upaya Untuk Melatih Pemahaman Konsep - Zidny Manaasika; Antomi Saregar; Trimo Saputro (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Physics education still faces challenges in helping students understand abstract concepts, particularly those related to light and sound waves, which are difficult to observe directly using conventional teaching materials. This study aims to develop a Virtual Reality learning medium integrated with the Cognitive Theory of Multimedia Learning for the topics of light and sound waves as an effort to develop CTML-integrated VR media that has the potential to support students’ conceptual understanding. This study employs a Research and Development method by applying the Borg and Gall model, stages 1–7. The research sample consists of 70 students from two MAN schools in Bandar Lampung. Data were collected through observation, interviews, subject matter expert validation, media expert validation, as well as student and teacher response questionnaires. The developed product consists of five interactive scenes that visualize light and sound wave phenomena in a three-dimensional and immersive manner. The integration of signal, redundancy, and sound principles within the VR medium was used to help manage visual and auditory information, thereby making the presentation of the material more focused, simple, and easy to understand. The results of this study indicate that the media received a feasibility rating of 90% from subject matter experts and 87% from media experts, as well as a response rate of 90% from students and 91% from educators, with a rating of highly feasible. This study found that CTML-integrated virtual reality media makes a positive contribution to the development of digital technology for physics education that takes into account students’ cognitive processes; however, further research is recommended to directly test the effectiveness of this media on students’ conceptual understanding.